Promoting Sustainable Military Tourism in Cimahi City: Fostering Conservation, Community Engagement, and Cultural Preservation - Sajid, Sriwinarsih Maria Kirana; Kirdsiri, Kreangkrai (Media Konservasi, 2024)
The military presence in Cimahi City, West Java, serves as a testament to its historical and cultural significance, reflecting an impressive cultural-historical heritage shaped by its militarized past. This authenticity as a military city (60% of the city population) provides a unique opportunity to develop a specialized tourism model that leverages military knowledge for sustainable social and economic growth. The integration of military cultural heritage into tourism activities poses a central challenge, particularly amidst a population where military personnel constitute a significant proportion and continue to play an active role. Employing a qualitative research methodology, this study combines a comprehensive review of relevant literature, historic references, in-depth interviews with the local business community, and cross-references with tourism models from other military cities. The study's outcomes focus on integrated tourism activities and attraction planning aimed at preserving the city's military spirit in collaboration with local residents, military personnel, and their families. This collaborative effort is envisioned to contribute not only to heritage conservation but also to fostering peace education and international cooperation, advocating against the glorification of war and conflict. This research emphasized the importance of heritage conservation, community participation, and sustainable resource management in the realm of cultural heritage and tourism development.